2018
DOI: 10.5152/tud.2017.48107
|View full text |Cite
|
Sign up to set email alerts
|

The association between variant urothelial histologies, pathological stage and disease specific survival in patients with bladder cancer

Abstract: Objective: We aimed to compare the oncological outcomes of patients with variant urothelial histologies (VH) with pure urothelial histology (PUH) in bladder cancer (BC) patients. Material and methods:This study includes 223 patients who underwent radical cystectomies (RCs) between September 2006 and July 2016 with complete follow-up data A retrospective screening was performed to identify the patients with PUH and VH. The primary outcomes of interest were pathological stage of disease at RC and disease-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“… 8 In Böyük et al’s study of 223 patients undergoing radical cystectomy, pathologic stage of disease, and presence of VH were found to be associated with lower CSS in the multivariate model. 9 In a meta-analysis of 23 studies involving 22 072 patients, VH was significantly associated with worse CSS (pooled HR 1.37, 95% CI). 10 On the other hand, Takemoto et al 11 found that VH was not effective on OS in both univariate and multivariate analyses in a series of 102 patients who underwent RC.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In Böyük et al’s study of 223 patients undergoing radical cystectomy, pathologic stage of disease, and presence of VH were found to be associated with lower CSS in the multivariate model. 9 In a meta-analysis of 23 studies involving 22 072 patients, VH was significantly associated with worse CSS (pooled HR 1.37, 95% CI). 10 On the other hand, Takemoto et al 11 found that VH was not effective on OS in both univariate and multivariate analyses in a series of 102 patients who underwent RC.…”
Section: Discussionmentioning
confidence: 99%